Folies a gauche: The Socialists' recent drubbing in France can be traced back to a misreading of the Mitterrand experiment - Halimi, S; Michie, J (Dryden Press, 1994)
The Socialists' recent drubbing in France can be traced back to a misreading of the Mitterrand experiment.